Families Living With Chronic Illness: Beliefs About Illness, Family, and Health Care. (May 2015) - Årestedt, Liselott; Benzein, Eva; Persson, Carina
Beliefs can be described as the lenses through which we view the world. With emerging illness, beliefs about the illness experience become important for nurses to understand to enhance well-being and healing. The aim of this study was to illuminate illness beliefs of families living with chronic illness. A qualitative design was chosen, including repeated narrative research interviews with seven Swedish families living with chronic illness. Hermeneutic analysis was used to interpret the transcribed family interviews. The result described beliefs in families, both within and across families. Both core beliefs and secondary beliefs about illness, family, and health care were revealed. Illness beliefs have importance for how families respond to and manage situations that arise from their encounters with illness. Nurses have to make space for and listen to families' stories of illness to become aware of what beliefs may support and encourage family well-being and healing. The Illness Beliefs Model provides a touchstone whereby nurses can distinguish both individual and shared beliefs within families living with chronic illness and provide ideas for family intervention if needed.